Optimality conditions for nonsmooth vector problems in normed spaces. (2nd June 2020) - Tinh, Phan Nhat
ABSTRACT: Using the approach of first- and second-order tangent sets as approximations of feasible sets and employing the concepts of approximations as generalized derivatives, we establish first- and second-order necessary and sufficient optimality conditions for solutions of nonsmooth vector problems in normed spaces and extend several well known results.